Crystal structure of Vibrio cholerae polysaccharide lyase RbmB bound to Vibrio polysaccharide (VPS) fragments provides insights into substrate recognition and cleavage - Ranjuna Weerasekera; Alexis Moreau; Xin Huang; Anna Potapova; Carmen Schwechheimer; Rajan Kandel; Yun Huynh; Owen Cannizzo; Ryan Gordon; Emma Gerace; Alexander J. Hinbest; Yiyan Yang; et al. (Proceedings of the National Academy of Sciences, 2026)
Exopolysaccharides are carbohydrate polymers secreted by bacteria to perform various roles including adhesion to surfaces, protection from environmental stressors, and as key components in the production of biofilms. The human pathogen Vibrio cholerae produces an exopolysaccharide called VPS, which is essential for the formation of its biofilm matrix through crosslinking interactions with a series of secreted accessory proteins. VPS consists of a repeating tetrasaccharide unit consisting of a uniquely modified α-L-gulose moiety (with N-acetyl, O-acetyl, and amide-linked glycine modifications). Encoded within the cluster containing the biofilm-production genes is a glycoside lyase called RbmB, which cleaves VPS and has been implicated in biofilm dispersal. Here we describe the ~2 Å X-ray structure of RbmB bound to tetrameric and octameric fragments of VPS representing 10 total monosaccharides of an enzyme–product complex. The structure, along with molecular dynamics simulations and complementary functional analyses of mutant proteins in vitro and in vivo, illustrates how recognition and cleavage of VPS relies on salt-bridging interactions between arginine residues in RbmB and the amide-linked glycine moiety uniquely found on the VPS L-gulose and a ~30° bend near the cleavage site that strains the scissile bond. We further present results regarding the localization of RbmB in V. cholerae cells, suggesting that cleavage of VPS by RbmB likely takes place in the periplasm. Sequence conservation suggests that homologous biofilm systems found in many Vibrio species likely utilize a similar VPS cleavage mechanism suggesting that RbmB could be an effective tool for dispersing biofilms across the Vibrio genus and beyond.